Essential laboratory skills for biosciences - Meah, Mohammed (John Wiley & Sons, 2011)
Essential Laboratory Skills for Biosciences is an essential companion during laboratory sessions. It is designed to be simple and give clear step by step instructions on essential techniques, supported by relevant diagrams. The book includes the use of particular equipment and how to do simple calculations that students come across regularly in laboratory practicals. Written by experienced lecturers this handy pocket book provides:Simple to follow laboratory techniquesClear use of diagrams and illustrations to explain techniques, procedures and equipmentStep by step wo.